Intraaortic Pulse Pressure Amplification in Subjects at High Coronary Risk - Temmar, Mohamed; Jankowski, Piotr; Peltier, Marcel; Mouquet, Vincent; Dębicka-Dąbrowska, Dorota; Hamida, Farah; Kawecka-Jaszcz, Kalina; Safar, Michel E. (Hypertension (Dallas, Tex. 1979), 2010)
Peripheral (brachial) pulse pressure normally exceeds central (aortic) pulse pressure but is a less powerful predictor of cardiovascular risk. The difference between the 2 variables, called pulse pressure amplification, has never been specifically studied between the proximal and distal aorta in coronary patients. Our goal was to determine aortic pulse pressure amplification in subjects at high coronary risk, with emphasis on associated renal and inflammatory factors. Blood pressure was measured invasively in the ascending aorta, abdominal aorta (at the level of kidneys), and iliac artery in 101 subjects (mean age, 63±11 years; 61 men) undergoing coronary angiography. Independently of age, sex, and the presence of coronary stenosis, the increase of pulse pressure between the ascending and terminal aorta was over 10 mm Hg (P<0.001), whereas mean blood pressure remained unchanged. Pulse pressure amplification did not differ significantly between patients with and without coronary artery stenosis. Irrespective of confounding variables, high pulse pressure measured in the ascending aorta and at the level of renal arteries (but not in the iliac artery) was independently related to proteinuria. The increase in pulse pressure from the ascending aorta to the renal level was negatively associated with leukocyte count, even after multivariate adjustment (β coefficient, −0.19; 95% CI, −0.39 to 0.0; P<0.05). Increased plasma creatinine and aortic pulse wave velocity were independently and positively correlated (β coefficient, 0.36; CI, 0.18 to 0.54; P<0.001). Independently of coronary atherosclerosis, aortic pulse pressure integrates the predictive value of aortic, inflammatory, and renal factors.